GAYA-GAYA KEPEMIMPINAN UNTUK MENINGKATKAN MUTU PENDIDIKAN - Hary Nur Syamsuddin (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
In the modern era, the very free technology and competition nowadays a leader's role is vital and very influential in the leader of an organization. A successful leader is a leader who can lead his subordinates to work together to achieve the vision, mission and goals of a school. A leader of one and the other must have a style or type of leadership that is not the same. A person's leadership style is the way a character stays or attitudes, relates, communicates, and interacts with others in influencing his subordinates to do something. The style can vary based on motivation, desire, ability, power or orientation towards responsibilities, tasks or specific people. Leadership style terssebut among his leadership style of charismatic, Paternalistic, Militeristik, Otoraktis, Laissez Faire, Populistis, Administrative, Democratic. The purpose or function of different leadership is to improve the quality of school principals, primary school principals, high school principals and high school principals to achieve and improve the quality of better education. The quality of education is to improve the quality of schools that can compete with other schools, professional teachers and students who excel in all fields both academic and non academic. Keywords— Leaders, leadership style, quality of education